2022
DOI: 10.24329/aspikom.v7i2.1169
|View full text |Cite
|
Sign up to set email alerts
|

Critical Discourse on Press Contribution to NTT Good Local Governance

Abstract: The contribution of local media in articulating its control function to restore people’s rights and encourage the implementation of good local governance cannot be separated from the professionalism and critical support of the media crew. This is because the relationship between local media and regional authorities is still prone to conflict, complex, and bound by certain emotional-cultural aspects. Using critical discourse analysis, this study examines specifically the editorial texts of two local mainstream … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…For example, a study previous study reported that a training workshop on manuscript writing positively impacted the knowledge of the participants and improved their writing skills (Hussain et al, 2020). Additionally, another pervious study found that a training program on writing scientific articles helped students improve their scientific abilities and produce manuscripts that were adapted to the journal template (Gobang et al, 2022;Hussain et al, 2020).…”
Section: Solutions For the Students' Disputesmentioning
confidence: 99%
“…For example, a study previous study reported that a training workshop on manuscript writing positively impacted the knowledge of the participants and improved their writing skills (Hussain et al, 2020). Additionally, another pervious study found that a training program on writing scientific articles helped students improve their scientific abilities and produce manuscripts that were adapted to the journal template (Gobang et al, 2022;Hussain et al, 2020).…”
Section: Solutions For the Students' Disputesmentioning
confidence: 99%
“…Prinsipnya, berita yang direproduksi media tidak bebas nilai (Gobang et al, 2022;Grafström & Rehnberg, 2022;van Dijk, 2013).…”
unclassified